Integrated weed control options under different sowing methods of isabgol (Plantago ovata Forsk) at transitional luni basin plain zone of Rajasthan - Reager, M.L.; Deora, N.S.; Tak, S.R.; Sanwal, R.C. (Annals of Agricultural Research, 2017)
A field experiment was conducted during rabi season of 2011-12 and 2012-13 at farmer’s fields and Krishi Vigyan Kendra, Jalore to study the effect of sowing methods and weed control optoins in isabgol. The experiment was laid out in a split-plot design with five replications. The treatments consisted of three main plots (sowing methods- broadcasting, sowing in line at 30 cm and sowing in line at 22.5 cm) and three sub plots (control, hand weeding at 30 DAS and post emergence application of isoproturon 600 g haâ€“1 at 20 DAS +hand weeding at 30 DAS). Sowing of isabgol cv. RI- 89 was done as per the sowing methods as broadcasting and different row spacing. Post emergence aplication of isoproturon at 20 DAS + hand weeding at 30 DAS in line sowing at 22.5 cm row spacing having statistically at par with hand weeding at 30 DAS in line sowing at 22.5 cm row spacing produced significantly maximum seed yield (1275.8 kg haâ€“1), straw yield (2665.1 kg haâ€“1) and net return (Rs 59392/- ha) over other weed control treatments in broadcast sowing and line sowing at 30 cm as well as 22.5 cm. However, in broadcast sowing, post emergence application of isoproturon at 20 DAS + hand weeding at 30 DAS enhanced seed, straw and net return over hand weeding at 30 DAS and unweeded control.